Structural Damage Identification Using Model Updating Approach: A Review - Sukri, Nur Raihana; Nurulakmar Abu Husain; Syarifah Zyurina Nordin; Mohd Shahrir Mohd Sani (Journal of Advanced Research in Applied Mechanics, 2021)
There have been countless studies to investigate structural damage identification. This field of study is sometimes referred to as structural health monitoring. Model updating approach is a non-destructive testing method that uses characteristic values related to structural models such as natural frequencies and mode shapes to identify the damage. Researchers over the last decade have focused on several model updating techniques for structural damage detection and identification. However, various methods can be used for model updating, and it can sometimes be quite confusing to choose which method to use for each case. Since this can have serious consequences, it is imperative to understand model updating better. This paper gives an introduction to structural damage identification, while brief information on finite element model updating is described and reviewed in terms of available methods and types of measured data. Here, the performance of different model updating methods utilized in structural damage identification is compared. This study has found that researchers in the iterative method extensively use modal data-based methods and frequency-based methods. The insights gained from this study may assist those who want a brief idea about model updating and its application in structural damage identification.